Perancangan E-Commerce Berbasis OpenCart untuk Promosi Produk Makanan Home Industry Di Kecamatan Aek Ledong - Arya Winaldi, Deni; Annas, Firdaus; Yusuf Armando, M (JOVISHE : Journal of Visionary Sharia Economy, 2024)
The digital transformation of marketing strategies presents a critical challenge for Micro, Small, and Medium Enterprises (MSMEs) in developing effective product promotion mechanisms. This research addresses the limited promotional channels for home industry food products in Aek Bange, Aek Ledong Subdistrict, by designing an innovative OpenCart-based E-commerce platform. Utilizing Research and Development (R&D) methodology with a ADDIE which includes the Analysis, Design, Development, Implementation and Evaluation development model, the study aims to create a robust web-based promotional media that enhances market accessibility for local entrepreneurs. The research methodology systematically examines the current limitations of traditional marketing approaches and leverages digital technology to provide sustainable solutions for MSME product promotion. By implementing an OpenCart-based e-commerce platform, the study explores the potential of digital technologies to bridge the gap between local producers and potential consumers. The developed platform undergoes rigorous validation processes to ensure its practicality, effectiveness, and user-friendliness. Empirical findings demonstrate that the OpenCart-based e-commerce solution significantly improves product visibility, market reach, and marketing efficiency for home industry entrepreneurs. The research reveals that digital platforms can effectively overcome geographical and promotional constraints faced by small-scale producers. Moreover, the study provides valuable insights into the transformative potential of technological interventions in supporting local economic ecosystems.The outcomes suggest that strategic technological integration can empower MSME actors, enabling them to introduce and market their products to broader audiences, thereby fostering economic growth and digital inclusivity in local communities.